Employee Engagement as a Mediator Between Empowerment, Motivation, and Performance in Bank Jatim Madiun - Suprapto, Yetty Fitria; Budiyanto, Budiyanto; Suhermin, Suhermin (Universitas Islam Kadiri, 2026)
This study investigates the influence of psychological empowerment and work motivation on employee performance at Bank Jatim Madiun, Indonesia, a regional branch operating in a competitive and service-driven banking environment. Employee performance, crucial to ensuring service quality and operational success, remains below institutional expectations despite ongoing efforts. The study addresses this issue by exploring whether psychological empowerment and work motivation directly affect performance and whether employee engagement mediates these relationships. Using a quantitative research design and a saturated sampling of 110 employees, data were collected via structured questionnaires based on validated instruments and analyzed using PLS-SEM with SmartPLS. Results show that psychological empowerment significantly enhances both engagement and performance, and that engagement mediates this relationship. In contrast, while work motivation positively affects engagement, it has no direct or indirect impact on performance. These findings imply that fostering psychological empowerment by promoting autonomy, competence, and purpose may be more effective in improving performance than relying on motivation alone. The study recommends that banks adopt empowerment-oriented human resource strategies to enhance engagement and organizational outcomes.